Finney and Miller's Principles of Accounting, Intermediate (Book). - Vargo, Richard J.; Spiller, Earl A. (The Accounting Review, 1975)
Reviews the book 'Finney and Miller's Principles of Accounting, Intermediate,' by Glenn L. Johnson and James A. Gentry, Jr.